(In)Efficient environmental policy with interacting pollutants - Kuosmanen, Timo; Laukkanen, Marita (Springer, 2011)
Many environmental problems involve the transformation of multiple harmful substances into one or more damage agents much in the same way as a firm transforms inputs into outputs. Yet environmental management differs from a firm s production in one important respect: while a firm seeks efficient input allocation to maximize profit, an environmental planner allocates abatement efforts to render the production of damage agents as inefficient as possible. We characterize a solution to the multiple pollutants problem and show that the optimal policy is often a corner solution, in which abatement is focused on a single pollutant. Corner solutions may arise even in well-behaved problems with concave production functions and convex damage and cost functions. Furthermore, even concentrating on a wrong pollutant may yield greater net benefits than setting uniform abatement targets for all harmful substances. Our general theoretical results on the management of flow and stock pollutants are complemented by two numerical examples illustrating the abatement of eutrophying nutrients and greenhouse gases
Keywords: Ma; Ys; ilmastonmuutokset; kustannus-hyötyanalyysi; ympäristösaasteet; ympäristöpolitiikka; climatic change; cost benefit analysis; pollutants; environmental policies; climate change; cost-benefit analysis; multiple pollutants; pollution controll